2018
DOI: 10.4102/sajr.v22i2.1315
|View full text |Cite
|
Sign up to set email alerts
|

Breast Imaging Reporting and Data Systems category 3 (probably benign) breast lesions detected on diagnostic breast ultrasound: The prevalence, outcome and malignancy detection rate in Zaria, Nigeria

Abstract: BackgroundProbably benign breast lesions in the Breast Imaging Reporting and Data Systems (BI-RADS 3) constitute a crucial category and a considerable number of all palpable breast masses. Local data concerning the outcome of such lesions in the Nigerian environment is almost non-existent.ObjectivesThe goal of this article is to report the frequency, outcome and malignancy detection rate among palpable breast masses that were categorised on ultrasound as BI-RADS category 3 (probably benign) according to the Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Our data showed that the overwhelming majority of histopathological results of the 2245 US-VAEB cases were benign breast disorders (88.5%), and only a small proportion (3.4%) was malignancies. The results are consistent with the literature [ 11 , 18 20 ]. It shows that criteria should be more strict to avoid unnecessary VAEB procedures for the patient’s clinical and economic benefit unless there is a specific request from the patient.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data showed that the overwhelming majority of histopathological results of the 2245 US-VAEB cases were benign breast disorders (88.5%), and only a small proportion (3.4%) was malignancies. The results are consistent with the literature [ 11 , 18 20 ]. It shows that criteria should be more strict to avoid unnecessary VAEB procedures for the patient’s clinical and economic benefit unless there is a specific request from the patient.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the diagnosis of B3 is much more challenging in clinical practice. It is reported that the approximate proportions of each biopsy results are normal/benign 70–98.89%, B3 < 10%, malignant < 2%, respectively [ 18 20 ]. The data indicate that most breast changes need not excision biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed that the overwhelming majority of histopathological results of 2245 VAEB cases were benign breast disorders (88.5%), and only a small proportion (3.4%) was malignancies. The results are consistent with the literature [11,[18][19][20]. It shows that criteria should be more strict to avoid unnecessary VAEB procedures for the patient's clinical and economic bene t unless there is a speci c request from the patient.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the diagnosis of B3 is much more challenging in clinical practice. It is reported that the approximate proportions of each biopsy results are normal/benign 70%-98.89%, B3 < 10%, malignant < 2%, respectively [18][19][20]. The data indicate that most breast changes need not excision biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…15 22 The remaining 1063 breast solid masses were probably benign, having a low (<2%) risk of malignancy; for these masses, definitive management depends on whether they are upgraded to malignant or downgraded to benign lesions. 23 For such cases, close short-term imaging follow-up would be ideal, especially in the initial 6 months after diagnosis. 24 Follow-up based on imaging rather than biopsy for lesions sonographically described as probably benign will reduce medical costs and unnecessary invasive procedures.…”
Section: Discussionmentioning
confidence: 99%